Sensor module for urban vehicle two way connection monitoring system/ Muhammad Ilyasaa Abdul Rahman - Abdul Rahman, Muhammad Ilyasaa (2015)
This technical paper put forward a sensor module for urban vehicle two-way connection monitoring device which will be designed to detect conditions such as the presence of human after the car is centrally locked or the car is moved when the engine is off. The objective of this project is to create a sensing module that able to detect presence of human after the car is centrally locked or the car is moved when the engine is off. Available current solutions to detect the living thing rely on action of people close to the vehicle because there is no owner-to-vehicle interconnection between owners and vehicles are separated. The project framework is divided into 2 main parts: living thing and impact detection. The sensing module will be interfaced with a microcontroller platform programmed with a set of algorithm. Scope of study will cover hardware and software for the device that will be placed in the vehicle as well as application development. The finding is the sensing module will be able to detect certain living thing such as baby, child or pet after the vehicle has been centrally locked.